Ways to Overcome Poverty and Income Inequality in the Context of New Global Challenges: the Most Important Conclusions for Ukraine - Andrii Ramskyi (Comparative Economic Research. Central and Eastern Europe, 2021)
The article examines the risks of deepening poverty and income inequality that arise from global challenges of population aging, job losses due to shrinking sales markets, trade wars, long-term quarantine and compliance with the safe distancing of people as part of restrictive measures against the spread of COVID-19, the nature of employment (remote work, temporary reduction of labor migration), and other norms in the fight against the dangerous contagious disease. Given the facts that the prevention of spreading and localization of dangerous diseases, their treatment, and the rehabilitation of patients affect all segments of the population, have negative effects on all areas of people's lives and also add to the increase of socio-economic risks, including poverty and inequality, the study of this issue is extremely relevant. The financial implications of these challenges for many households lead to falling real incomes, and an increase in costs and debts, and their non-repayment, which generally cause sudden poverty and increasing inequality of income and property. Purpose of the article: To investigate the risks of poverty, including sudden poverty, the inequality of household incomes amid the fight against the COVID-19 pandemic, and it identifies ways to overcome them. Methods: A review of the scientific literature, a presentation of statistical data, and statistical research. Findings & Value added: As a result of research, a list of new risks of poverty and income inequality is outlined, and preliminary assessments of the consequences of the COVID-19 for households are summarized; signs of short-term loss are generalized; the solvency of households as a possible precondition for sudden poverty is evaluated; cross-country comparisons of poverty risk are made; the scheme of state aid to improve living standards of people during the outbreak of new dangerous diseases in the EU and Ukraine is generalized; ways to overcome poverty and income inequality are substantiated to restore the resilience of financially vulnerable households and ensuring the development of human capital.
Keywords: J61; E24; I32; F65; 330; household finances; financial stability; struggle with poverty; inequality; labor migration; unemployment; COVID-19 pandemic; economic consequences of globalization; state support of households